Diagnostic accuracy of septic markers for neonatal sepsis - Thermiany AS; W Retayasa; M Kardana; IN Lila (Indonesian Pediatric Society Publishing House, 2016)
Background Neonatal sepsis is a major cause of morbidity and mortality. A positive blood culture is the gold standard for diagnosis of neonatal sepsis. The signs and symptoms suggesting neonatal sepsis are non-specific. There is no rapid and reliable laboratory test findings for confirmation of etiologic diagnosis. Clinical signs, symptoms, and laboratory examinations are not perceived as sensitive or specific for diagnosis of sepsis. Objective The purpose of this study was to evaluate the accuracy of the septic markers for diagnosis of neonatal sepsis. Methods Blood culture was used as gold standard to compare septic markers to diagnose neonatal sepsis. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive and negative likelihood ratio (LR), and accuracy were calculated. Results We identified 130 cases suspected of neonatal sepsis during September 2005 until March 2006. Four patients were excluded because of major congenital anomalies. The mean age was 2.2 days and 51.6% were boys. We found fifty six (44.4%) neonates have positive blood culture. All of septic markers had sensitivity more than 80%. Immature to Total Neutrophil ratio (Iff) ratio had the highest sensitivity (96.4%) and C-Reactive Protein (CRP) had the lowest sensitivity (80.4o/o). Combination among leukocyte count, thrombocyte, and Iff ratio had the highest sensitivity (sensitivity was 85. 7%, specificity was 97.1 o/o, positive predictive value was 95.9%, negative predictive value was 89.5%, accuracy was 94.4%, and positive likelihood ratio was 30.0). Conclusion Septic markers can be used in the diagnostic evaluation of neonates with suspected sepsis.